THE EVALUATION OF POLICY EFFECT ON GENERIK MEDICINE PRICES 2010 TOWARD SELLING PRICE, THEIR AVAILABILITY AND AFFORDABILITY IN PRIVATE PHARMACIES IN KABUPATEN JEMBER - Ika Norcahyanti; Djoko Wahyono; Tri Murti Andayani (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
One of government’s efforts to guarantee people access on essential medicine is by applying a policy concerning with generic medicine prices. The purpose of the research was to find out the variation and the ratio of generik and branded medicine selling prices in comparison with Harga Jual Apotek (HJA) – Pharmacy Selling Price – based on the regulation of Health Mi n i s t r y and International Reference Prices (IRPs) 2010 and their availability and affordability in some private pharmacios in Jember. The research design was a descriptive non experimental. The data collected retrospectively toward generik and branded medicines mostly prescribe during April-August 2010 include their prices and affordability. Research result showed that the ratio of generik medicine selling price toward HJA was 0.14-9.09 times and 0.26-114.06 times. On the other hand, the ratio of generic and branded medicine selling price toward IRPs 2010 was 0.03-16.67 times and 0.09-501.88 times. In 50 kinds of mostly prescribed medicines, 35 of them were generik medicines with affordibility range 11.4%-93.2%. In the matter of affordability, it needs 1 working day to do a therapy using generik medicines for diabetes mellitus, hypertension, hypercholesterolemia, rheumatoid arthritis, and infection cases. In contrast, it requires 1-35 working days to do those therapies using branded medicines with Regional Minimum Salary of Rp.33.200.00 for each working day. Keywords : generic medicine price policy, pharmachy selling price, medicine avalaibility, medicine avordbility,Jember.